PENINGKATAN KEMAMPUAN GURU BAHASA INGGRIS SMP NEGERI 2 TEBINGTINGGI DALAM MELAKSANAKAN PEMBELAJARAN CONTEKTUAL TEACHING AND LEARNING MELALUI KEGIATAN SUPERVISI KLINIS - Sinur Hutagaol (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
The purpose of this study is to improve the ability of English teachers in conducting the learning process that uses the concept of contextual learning. This study uses Kemmis M Targart research, consisting of 2 cycles in which each cycle consists of activities of planning, implementation, observation and reflection. Data collection techniques in this study are using interviews, observations and questionnaires. This research is said to be successful because of the pre cycle where from the samples taken, from five teachers who were guided by researchers, not one person has ever applied contextual learning in teaching. The success rate of this study is 88.8%. Based on the results of these studies then through clinical supervision activities can increase teacher commitment in implementing learning Contextual teaching and Learning and this research is said to be successful.Keywords: Ability, CTL, Clinical Supervision